The impact of macroprudential policy instruments on financial stability in Southern Europe - Eva Lorenčič; Mejra Festić (Naše gospodarstvo / Our Economy, 2022)
This paper is a contribution to the body of research examining the impact of macroprudential policy instruments on financial stability. The following hypothesis was tested (H1): Macroprudential policy instruments (household borrowing costs; interbank loans as a percentage of total loans; loan to deposit ratio; leverage ratio; and solvency ratio) enhance financial stability, as measured by credit growth, in four southern European economies (Greece, Italy, Portugal and Spain) from Q4 2010 to Q4 2018. The empirical results of this study suggest that, of the investigated macroprudential policy instruments, household borrowing costs, interbank loans as a percentage of total loans and loan to deposit ratio exhibit the predicted impact on credit growth rate. Leverage ratio and solvency ratio do not exhibit the expected impact on the response variable. Moreover, only three out of the five explanatory variables are statistically significant in the model. Consequently, it is not possible to confirm or reject the hypothesis based on the available data and results.
Keywords: E58; G28; E60; E44; 330; macroprudential policy; macroprudential instruments; systemic risk; financial stability